Difficulty in Memorizing the Qur'an among Grade II Students at SDIT Salman Al Farisi: A Case Study - Ahmad Fauzan; Dariyanto Dariyanto (Universitas Cokroaminoto Palopo, 2025)
This study explores the difficulties encountered by second-grade students at SDIT Salman Al Farisi in memorizing Surah Al-‘Asr (QS. 103:1–3), focusing on four major aspects: Qur’anic reading ability, memorization fluency, articulation accuracy, and mastery of tajweed rules. The research employed a qualitative case study approach to provide an in-depth understanding of the phenomenon. Data were collected through direct classroom observation, in-depth interviews with three purposively selected students and their tahfidz teacher, as well as documentation analysis of academic records and progress notes. The findings revealed that limited Qur’anic reading skills significantly hindered the memorization process. Students who struggled with decoding words, connecting syllables, and applying vowel length (mad) rules could not fully concentrate on retention and comprehension. Low fluency was another challenge, reflected in frequent hesitation, stammering, and confusion between verses, largely due to insufficient repetition (muroja’ah) and lack of independent practice at home. Articulation difficulties were evident in the inaccurate pronunciation of several hijaiyah letters such as dza, shod, ‘ain, and tsa, which reduced the clarity and meaning of recitation. Moreover, insufficient mastery of tajweed and makhraj rules, particularly in applying ghunnah, idgham, and correct vowel length, resulted in repeated errors across all three students. The study confirms that these four aspects are deeply interconnected, where weakness in one area exacerbates problems in the others. It underscores the need for integrated pedagogical interventions that combine talaqqi-based learning, structured articulation drills, comprehension-based methods, and systematic repetition schedules. Parental involvement was also found to be essential in reinforcing practice outside the classroom. Overall, the research highlights that successful Qur’an memorization in elementary schools cannot be achieved through isolated teaching strategies but requires a comprehensive, collaborative approach between teachers, students, and parents. Future research is recommended to expand the sample and evaluate specific intervention models to strengthen both the cognitive and spiritual outcomes of tahfidz learning.